Semen Washing and Intrauterine Insemination for Reducing the Risk of Human Immunodeficiency Virus Transmission in Serodiscordant Couples: A Cross-sectional Study - Duru Shah; Raj Harjani; Vishesha Yadav (Wolters Kluwer Medknow Publications, 2024)
Background: Antiretroviral therapy has helped human immunodeficiency virus (HIV)-infected people live an enhanced quality of life and attempt for a pregnancy, without placing their partner at risk. Although periconceptional pre-exposure prophylaxis for the uninfected partner and consistent antiretroviral therapy for the HIV-infected partner are important to prevent HIV transmission, semen washing could be a great option to further reduce the semen viral load. Aim: The aim of this study were as follows: to determine if semen washing with intrauterine insemination provides an added safety net to HIV-serodiscordant couples when the male partner is HIV-infected and virally suppressed and to determine if the U = U concept (undetectable = untransmittable) holds true in virally suppressed HIV-infected males. Settings and Design: This was an observational study conducted in seropositive HIV men under treatment with highly active antiretroviral therapy (HAART) in collaboration with Metropolis Laboratory, a CAP recognised private Healthcare Laboratory in Mumbai, India. Materials and Methods: Blood and semen samples were collected from a total of 110 adult HIV-1-infected males virally suppressed on HAART. These samples were processed to assess the viral load in plasma as well as raw and processed semen fractions. Statistical Analysis Used: Descriptive statistics were used to analyse the data. Results: Only men with plasma viral loads < 1000 copies were selected in our study. Out of the 110 HIV-infected individuals, 102 (92.73%) patients had undetectable (<20 copies/ml) plasma viral load while 8 (7.27%) patients had a detectable (>20 copies/ml) viral load, who were excluded from the study. In the virally suppressed 102 men, the raw semen samples of 100 men showed an undetectable viral load, while 2 samples showed detectable contamination, even though their plasma samples from the blood showed a viral load of <20 copies/ml. The semen was then separated into the sperm and the seminal plasma samples. The seminal plasma had <20 copies/ml in 95 samples (93.14%) but a detectable viral load in 7 (6.86%) samples. After subjecting all the 102 processed (post-wash) sperm samples to quantitative analysis, an undetectable viral load of <20 copies/ml was found in all the samples. Thus, the raw sample (prewashed),seminal plasma and processed (postwash) samples were evaluated. The post-wash sperm sample showing zero contamination was frozen for intrauterine insemination (IUI) in the uninfected female partner. Conclusions: Semen washing with IUI should be advocated as a safe, efficacious way to increase the safety net and to further reduce the minimal risk of HIV transmission in serodiscordant couples in addition to the U = U concept.